Nieklasyczne metody estymacji przedziałowej wag stylu Sharpe'a na przykładzie modeli analizy stylu zarządzania OFE - Orwat, Agnieszka (Non-Classic Methods of Interval Estimation of Sharpe Style Weights Based on The Example of OPF Management Style Analysis Models, 2008)
The style analysis worked out by William Sharpe is a method of effectiveness describing, enabling drawing conclusions on impacts on funds' investment portfolios. Interval estimation of Sharpe style weights is the key aspect of Style Analysis method application. The consequence of the existence of restrictions for Sharpe style analysis model parameters is the fact that MNK estimators of style weights do not have an asymptotic normal distribution. Moreover, classical methods of standard errors and confidence intervals obtaining for Sharpe style weights are statistically justified only in the case, when each of estimated weights belongs to the interior of parameter space. So it is important to use such methods, for which distributions of estimated parameters and confidence intervals are statistically justified in the presence of constraints irrespective of actual values of style weights. The paper aimed at implementation of Andrews's method in interval estimation of Sharpe style weights based on the example of management style analysis models of selected Polish Open Pension Fund (OPF).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 302-311